Application of artificial intelligence in dentistry: Literature review - Cacñahuaray-Martínez, Génesis (2021)
The application of artificial intelligence (AI) in the dental field was reviewed in this article. The objective was to review the evidence on artificial intelligence and its application in the different dental specialties. A search was carried out on Medline/PubMed, Scopus and Web of Science databases from 2017 to 2021. Three hundred and twenty-one articles were found, of which 62 were selected and allowed the application of AI in six specialties: periodontology, implantology, forensic dentistry, oral medicine and pathology, orthodontics and diagnostic/cariology/endodontics. The specialty of diagnosis/caryology/ endodontics had more articles on the topic of AI and convolution neural network was the type of AI most used. It was concluded that AI is being widely used in dentistry showing promising results as they show an accuracy equivalent to that of different trained specialists and in some cases they overcome human errors showing excellent results.